Indoda iyanyamezela (a man perseveres): Exploring the perceptions, experiences and the psycho-social challenges of Xhosa young men in the Western Cape who have transitioned from adolescence to manhood without present or involved fathers - Moshani, Nomakhawuta Lettitia (Department of Psychiatry and Mental Health, 2023)
BACKGROUND: Father absence or uninvolvement is a growing problem worldwide, which not only negatively influences child development, but also the masculine identity formation of boy children. South Africa is one of the countries that has high levels of father absence, yet there has been scant research which particularly focuses on the perceptions, experiences and psycho-social challenges experienced by young men with absent fathers. Thus, the aim of this study was to explore the perceived influence of father absence or uninvolvement on Xhosa young men who have transitioned from adolescence to manhood. The first objective was to explore the perceptions, experiences and the psycho-social challenges of Xhosa young men in Khayelitsha, Western Cape who have transitioned from adolescence to manhood without present or involved fathers. The second objective was to explore Xhosa male elders' perceptions of the experiences and challenges of Xhosa young men who culturally transition from adolescence to manhood without present or involved fathers. The third objective was to identify the support needs of Xhosa young men before, during and after transitioning from adolescence to manhood in the absence of a present or involved biological father. METHODOLOGY: Using Bronfenbrenner's ecological systems theory as a conceptual framework, the study employed a qualitative approach to investigate factors that shape and influence experiences of Xhosa young men with absent or uninvolved fathers at individual, family, community and societal levels. Semi-structured in-depth individual interviews were conducted using interview guides covering various topics: family life; conceptualisation of manhood and fatherhood; father absence in Xhosa communities and its causes and impacts; the value of social fathers as well as the possible preventative interventions at different levels of the society to promote father presence or involvement and mitigate the impact of father absence. All interviews took place at different venues offered by community organisations in Khayelitsha (Ilitha Park, Site B and Nkanini) in the Western Cape province. They were conducted in isiXhosa, audio-recorded, transcribed and translated into English for analysis. Data analysis was conducted using thematic analysis utilising the NVivo 12 software package. During transcription, three researchers read the transcripts and developed an initial coding framework which was then used to code the rest of the data, making adjustments as necessary. The data were categorised thematically paying attention to dominant themes that addressed the research questions, while being open to additional themes arising in the data, and this process occurred until no new themes emerged. ETHICAL APPROVAL: The ethical approval of this study was provided by the UCT Human Research Ethics Committee (HREC 654/2018). RESULTS: The interviews were conducted with 22 Xhosa young men with absent or uninvolved fathers (ages 18-22) and five Xhosa male elders (ages 55-73). Due to the sensitivity of the topic initiation, a vignette was used to avoid directness. The main perceptions, experiences and psychosocial challenges of Xhosa young men who have transitioned from adolescence to manhood without present or involved fathers, were synthesised as follows: (i) The meaning given to cultural male circumcision by young men and elders were its individual family benefits. (ii) The challenges of Xhosa patriarchy, a father's role, and his absence, and paternal connection needs during initiation: planning, masculine guidance and protection, emotional and cultural support. (iii) The significance of the fatherly role and implications of father absence before and beyond initiation: the traditional and modern role. (iv) Barriers to father presence or uninvolvement: financial constraints, maternal gate-keeping and mother's negative attitudes. Using Bronfenbrenner's ecological systems theory, the support needs of Xhosa young men without present or involved fathers before, during and after transitioning from adolescence to manhood were identified as follows: (i) At the microsystem level, single mothers and maternal families of Xhosa young men need to be open regarding father absence, acknowledge the pain it causes and avoid maternal gatekeeping and paternal identity concealment. However, they also need to receive psycho-social support in order to be able to link the young men with social fathers, especially around initiation. (ii) At the mesosystem level, the social institutions such as churches, schools and sports clubs should have awareness regarding father absence or uninvolvement as a social problem in order to be sensitive towards the emotional needs of children with absent or uninvolved fathers. (iii) At the exosystem level, there is a need for fathers' environments (such as family, friends and the workplace) to encourage and foster lifestyles that promote father presence or involvement. (iv)At the macrosystem level, the media should raise awareness of father absence, and there must be policies and programmes that promote egalitarian parenting. (v) At the chronosystem level, there is a need to embrace and practice the modern fatherhood role which requires the father to be warm, spend quality time and have strong communication with his children. CONCLUSION: Cultural initiation is a crucial time for emotional and cultural growth which largely contributes to the development of manhood identity; it benefits the person on an individual and family level. However, this study notes that initiation comes with advantages and disadvantages for the Xhosa young men. It is a vehicle for growth, but also serves as a reminder of the vacant paternal role during this culturally significant process, especially in the midst of maternal gate-keeping and paternal identity concealment issues. Furthermore, in the course of their lives, the young men also experience loss related to not being exposed to the various positive roles a father would play, including the roles of disciplinarian, provider and the nurturer. Even though social fathers and strong maternal kin support could help Xhosa young men to cope better, the void of the biological father remains unfilled, especially around the period of initiation due to the emotional, cultural and financial implications of the ritual. This study shows that the young men could experience depression, be suicidal, have anger and resort to substance use when not supported. There is thus a need for multi-dimensional interventions to address these issues. These should start with psycho-educational support for maternal families to empower them to be supportive towards the emotional and cultural needs of the young men as the families do not always possess the necessary skills to support a child in this predicament. Absent fathers also need to be engaged in order to understand the reasons leading to their disengagement, and to sensitise them regarding the consequences of their absence for them to better understand the permanence of fatherhood. Advocacy is needed to make the wider society aware of the support needs of Xhosa young men who go through initiation in the absence of a father. Finally, the strategies that seem to yield positive results in managing father absence need to be strengthened, namely: strong maternal family support, social fathering, counselling and mentorship.